2019
DOI: 10.1021/acs.jpcb.9b07627
|View full text |Cite
|
Sign up to set email alerts
|

Orientational Dependence of Cofacial Porphyrin–Quinone Electronic Interactions within the Strong Coupling Regime

Abstract: We examine the relative magnitudes of electronic coupling H DA in two face-to-face rigid and diastereomeric (porphinato)­zinc­(II)–quinone (PZn–Q) assemblies, 1β-ZnA and 1β-ZnB, in which the six quinonyl carbon atoms lie in virtually identical arrangements relative to the PZn plane at sub-van der Waals donor–acceptor (D–A) interplanar separations. Steady-state and time-resolved transient optical data and computational studies show that minor differences in relative D–A cofacial orientation give rise to dispara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The dependence of V RP on the geometries is documented in the computational studies. 45,52 Unfortunately, the current data set and the analyses could not rigorously test this point, and it is an area of further investigation. Acknowledging that the errors are associated with both of the analyses, our current work still supports the design principle of magneto-optical probes based on eq 1.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The dependence of V RP on the geometries is documented in the computational studies. 45,52 Unfortunately, the current data set and the analyses could not rigorously test this point, and it is an area of further investigation. Acknowledging that the errors are associated with both of the analyses, our current work still supports the design principle of magneto-optical probes based on eq 1.…”
Section: Resultsmentioning
confidence: 98%
“…Briefly, we assumed that CS, bCR, and CR S , all on the singlet potential surface, can be adequately described for all with the same parameters; we have V RP‑n,S = V RP‑S1 ∼ V RP‑GS . This assumption is in part supported by the fact that reorganization energies for intramolecular CS and CR reactions are typically uniform. , In the fitting procedure, we fixed the internal reorganization energy (λ V = 0.27 eV) based on the DFT calculations and determined V RP‑n,S and the solvent reorganization energy λ S : we obtained V RP‑n,S = 13 ± 4 cm –1 and λ S = 0.64 ± 0.05 eV. The determined λ S is in a reasonable agreement with the estimate based on the Marcus model based on a dielectric continuum model, λ S of 0.6 ± 0.1 eV within the solvent systems used in the analysis ( D S = 3.75–4.81) …”
Section: Results and Discussionmentioning
confidence: 99%
“…The cofacial donor-acceptor orientation has proven crucial for regulating the electronic communications and thus the excited state dynamics of push-pull dyads, which is an important topic in the studies of charge-separated states [37][38][39]. However, its implications on TADF properties have been scarcely explored.…”
Section: Introductionmentioning
confidence: 99%
“…Such interactions are quantitatively expressed by the electronic coupling ( H 12 ), which is an off‐diagonal Hamiltonian matrix element of the secular determinant in the two‐state model 1 . It has been revealed that the magnitude of H 12 in the π ‐stacked system in which the donor and the acceptor are juxtaposed is significantly affected by the subtle differences of donor–acceptor distance and mutual orientation 2 . Since the π ‐stacked aromatic frameworks are widely used in modern organic electronic devices, an understanding regarding charge transport behavior toward the longitudinal direction rather than the transverse one becomes more important 3–12 .…”
Section: Introductionmentioning
confidence: 99%